An analysis of China’s response towards Uighur Muslims in Xinjiang - Ramodibe, Tokologo (My University, 2020)
Uighur Muslims in China represent a unique group of Muslims living in China due to the fact that they predominantly receive the bulk of the Chinese government’s repressive policy. China’s repressive policy towards Uighurs in Xinjiang has not only turned the province into a police and apartheid state, but the repressive policy has grossly violated Uighur Muslims’ fundamental human rights. While attempts have been made to explain the cause of China’s state response towards Uighurs, this research report is unique in that it posits that there exists more than one single cause of China’s state response. Namely, these causes are: islamophobia, ethnicity, terrorism and Chinese state security. Together, these four causes provide some clarity in understanding China’s treatment of Uighur Muslims
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Arts in International Relations, 2020